Modelling inborn errors of metabolism in zebrafish. Issue 4 (6th May 2014) - Wager, Kim; Mahmood, Fahad; Russell, Claire
Abstract: The majority of human inborn errors of metabolism are fatal multisystem disorders that lack proper treatment and have a poorly understood mechanistic basis. Novel technologies are required to address this issue, and the use of zebrafish to model these diseases is an emerging field. Here we present the published zebrafish models of inborn metabolic diseases, discuss their validity, and review the novel mechanistic insights that they have provided. We also review the available methods for creating and studying zebrafish disease models, advantages and disadvantages of using this model organism, and successful examples of the use of zebrafish for drug discovery and development. Using a zebrafish to model inborn errors of metabolism in vivo, although still in its infancy, shows promise for a deeper understanding of disease pathomechanisms, onset, and progression, and also for the development of specific therapies.